Wear Analysis On Different Customized Twist Drill Bit Designs In Drilling Cfrp Panel - Hashimi, Nur Hatin Raihana (Universiti Sains Malaysia, 2021)
Drilling is one of the most common machining technique being practiced in the aviation industry especially during the fabrication of aircraft parts and structures by using twist drill as the cutting tool and CFRP composite laminate as the workpiece. However, drilling is still consider as one of the most challenging process as these recent issues lead to the occurrence such as delamination defect and also rapid tool wear which in the end degrade the hole quality produced. One of the reasons that lead to such issues might be due to the incompatibility between the cutting tool used as well as the composites manufactured. Therefore, in this study, wear analysis on different customized twist drill bit design in drilling CFRP panel are being investigated. It is based on the thrust force signature and temperature form when drilling different machining holes by using three different cutting tools which are burnishing (B), subland drill reamer (SB) and also tapered web drill bit (TW). The purpose is so that manufacturers can stay alert by changing their drill bit if the thrust force and temperature value obtained is nearer to the values that cause wear cutting tool. The machining parameters used in this study is constant as the drilling take place at 3000 rev/min spindle speed and 0.05mm/rev feed rate. The results obtained were then tabulated and analyzed with proper justifications before reaching to the conclusion.